The effect of aqueous extract of orchid root on the structure of ovary and hypothalamic-pituitary-gonadal hormones in polycystic ovary syndrome rat model: An experimental study - Hassanali Abedi; Armin Zarrin-Mehr; Bahareh Ebrahimi; Hoda Haghshenas; Negar Parvin; Hossein Kargar Jahromi (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Some medical conditions, including polycystic ovarian syndrome (PCOs), may lead to infertility. In PCOs, hormonal imbalance is significant. Antioxidants such as natural antioxidants have many health benefits, including positive effects on hormone production. Objective: Since herbal medicines are more acceptable to people, the present study was designed to evaluate the effect of an aqueous extract of orchid (SA), with antioxidative effects, on the structure of the ovary and the hypothalamic-pituitary-gonadal axis hormones and free testosterone in PCOs rats. Materials and Methods: In this experimental study, 64 healthy female Wistar rats (180-200 gr) were randomly divided into 60 and 89 day control groups, PCOs, and 4 PCOs + SA groups that received 40, 80, 160, and 320 mg/kg of SA. Serum levels of gonadotropin-releasing hormone, estrogen, progesterone, testosterone, follicle-stimulating hormone, and luteinizing hormone were measured. In addition, the ovaries were extracted and examined histologically. Results: The amount of primordial, primary, secondary, and Graafian follicles and serum levels of follicle-stimulating hormone and progesterone hormones decreased in PCOs groups, while atretic follicles and the serum levels of gonadotropin-releasing hormone, luteinizing hormone, estrogen, and free testosterone were increased. SA at different doses regulated hormonal and histological imbalances caused by PCOs, and 320 mg/kg was the most effective. Conclusion: The aqueous extract of orchids root can have a positive effect on the improvement of polycystic ovary syndrome. This effect can be achieved by regulating the level of sex hormones and correcting follicular abnormalities in the ovarian tissue.